Le Capital Immatériel : nouveau mode de gestion, à l’épreuve des mutations mondiales, dont la crise sanitaire, due à la « Covid-19 » Cas des Entreprises Marocaines - MAZOUZ , Salim; BENAMMI , Mohamed Hamza (Revue Internationale du Chercheur, 2021)
The global economy operates in an unstable environment characterized by rapid changes to which companies, but also other entities, will have to adapt. The new global context highlights knowledge, education, knowledge, technological revolutions, innovation, all of them have a highly intangible character, we speak then of a new economy "The knowledge economy". Faced with this observation, the performance of companies has become intimately entwined to its ability to protect itself against economic changes, both national and global. In the current context, the pandemic, due to the "Covid-19", is an unprecedented experience for contemporary companies, accentuated by the increased risk of bankruptcy. To this end, the primary objective of this contribution is to shed light on the consideration of intangible capital by companies, as well as its valuation, in particular its impact on their ability to adapt and their performance. To do this, we opted for a survey, carried out among Moroccan companies, whose sample consists of 96 companies, including 70 responses.